Institutional Transformation of Traditional Muslim Philanthropy in Ponorogo - Unun Roudlotul Janah; Dede Nurohman; Agus Eko Sujianto; Tri Cahyani, Yutisa (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Ponorogo, 2025)
Introduction: Nahdlatul Ulama (NU) is one of the largest Islamic organizations in Indonesia that plays a strategic role in philanthropic activities through various social programs for the community. However, studies on the institutional transformation of philanthropy in traditional Muslim communities at the local level are still limited in the literature. This study aims to fill this gap by exploring (1) the ideas and concepts behind the institutional transformation of philanthropy in traditional Muslim communities in Ponorogo, and (2) the dynamics of the transformation process. Research Methods: This study uses a qualitative approach with a descriptive-analytical design, involving informants from NU administrators, philanthropic institution managers, and Nahdliyin community leaders. Data analysis was conducted through a thematic coding model to interpret patterns of ideas, values, and institutional innovation. Results: The results show that the institutional transformation of philanthropy is influenced by immanent changes in religious values and external contact with modern institutions. Conclusion: These dynamics are reflected in institutional innovations, particularly the establishment of Lazisnu and its rebranding as NU Care–Lazisnu, with the involvement of religious leaders as strategic communication channels.